Beyond Reality: The Metaverse as a Strategic Tool for Branding and Marketing Innovation - Guimarães, Larissa de Azevedo (2024)
Metaverse has rapidly emerged in the last years as a transformative arena for companies seeking innovative alternatives to position their brands and engage customers in immersive experiences. As a groundbreaking frontier for marketing efforts to redefine brand positioning and user experience, the metaverse and related technologies that enable virtual and augmented reality transcends traditional digital marketing boundaries, as brands currently aim for creative interactive offerings to improve brand-customer relationship in more dynamic environments. The present study goes even further on the current body of knowledge regarding brand positioning in the metaverse employing a mixed method approach (qualitative and quantitative) combining insights from experts, collected through one-to-one interviews, with a quantitative study tested using structural equation modeling (SEM). By combining in our theoretical model, the influence of social media marketing activities’ components, by Bilgin Y. (2018), and the unified theory of acceptance and use of technology (UTAUT), by Venkatesh et. al (2003; 2012), our study presents an innovative approach to the metaverse as a resourceful alternative for marketing teams and practitioners. Businesses are increasingly exploring the potential of the metaverse, discovering novel opportunities to craft memorable brand experiences, foster deeper connections with consumers, and pioneer innovative forms of virtual interaction and online communities.